Analysis of factors influencing use behavior on e-commerce users in Batam City - Edric Colin Hwang; Elfan Wahyu Mulyana (Enrichment : Journal of Management, 2022)
This study was studied with the intention of examining what factor influence the use behavior e-commerce in Batam City. The object of research in this study is the people of Batam City who are e-commerce users. The independent variables in this research study are performance expectancy, effort expectancy, social influences, hedonic motivations, and habits. The dependent variable used in this study is use behavior and is equipped with an intervening variable, namely use intention. The research conducted by the author in this study applies a comparative causal method with a quantitative approach. In collecting samples purposive sampling is the technique used and the results of sample collection are processed and analyzed with smart PLS. The results of this study indicate that habits, and social influences can lead to behavioural intentions so that they can encourage use behavior towards the use of e-commerce. If people who use e-commerce are considered to have become a habit, it will definitely be able to generate behavioural intentions and will lead to use behavior e-commerce. This also applies to social influence, if the social influence is stronger, it will encourage people to behavioural intention e-commerce so that they will carry out use behavior in e-commerce applications.